2009
DOI: 10.1055/s-0029-1215043
|View full text |Cite
|
Sign up to set email alerts
|

Where has the tumor gone? The characteristics of cases of negative pathologic diagnosis after endoscopic mucosal resection

Abstract: In the case of pathologically negative findings at EMR, tumors might have been small enough to have been removed by the previous forceps biopsy. However, the possibility of sampling error or of a different location should be considered. Furthermore, appropriate communication between endoscopists and pathologists is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
5
16
0
Order By: Relevance
“…Therefore, this study is an attempt to disclose our findings in this lesser known field. In our study, NRD was detected in 3.2 % (143/4401) of analyzed lesions, which is comparable to the results of previous studies [8,9,19]. The mean endoscopic size of the lesions observed in the enrolled cases was much smaller than that of the other gastric neoplasms (12.66 ± 8.89 mm), which were removed by ER in our institution during the same period.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, this study is an attempt to disclose our findings in this lesser known field. In our study, NRD was detected in 3.2 % (143/4401) of analyzed lesions, which is comparable to the results of previous studies [8,9,19]. The mean endoscopic size of the lesions observed in the enrolled cases was much smaller than that of the other gastric neoplasms (12.66 ± 8.89 mm), which were removed by ER in our institution during the same period.…”
Section: Discussionsupporting
confidence: 89%
“…According to previous studies, 6.4-30.1 % of biopsy-proven low-grade adenomas were diagnosed as high-grade adenomas and 3.8-11.0 % as adenocarcinomas after ER [6,7]. Meanwhile, some studies addressed that no residual disease (NRD) was found in the specimen after ER in some patients who were diagnosed with gastric adenoma, carcinoma, or atypical gland by EFB [8,9]. The incidence of NRD after ER of gastric neoplasms has been reported to be as low as 3.2-3.4 %, but only limited information is available in the literature at present.…”
mentioning
confidence: 99%
“…One less frequently mentioned factor is the possibility of no residual tumor in the resected specimen. Kim et al [34] reported that there was no residual tumor in 3.2 % (20/633) of endoscopically resected gastric dysplasia or EGC. No residual tumor after ESD can be due to complete removal of the lesion at biopsy, pathology overestimation, and incorrect localization [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, previously mentioned progression rates of low-grade dysplasia in large series seem discrepant with these findings. Moreover, in 3% to 5% of gastric neoplasia diagnoses on forceps biopsy tissue, EMR does not confirm this diagnosis [209,210]. Nevertheless, EMR may be considered in patients with low-grade dysplasia with an endoscopically defined lesion, in order to obtain a more accurate histological diagnosis.…”
Section: Surveillancementioning
confidence: 99%